Delayed Umbilical Cord Clamping at Birth: Beneficial for All Babies. Issue 4 (July 2017) - Killion, Molly M.
Abstract : Delayed clamping of the umbilical cord for at least 30 to 60 seconds at birth of vigorous term and preterm babies is now recommended by the American College of Obstetricians and Gynecologists. Our maternity nursing expert, Molly Killion, explains the rationale for this practice change.